2011
DOI: 10.5539/ies.v4n4p84
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem and Hopelessness, and Resiliency: An Exploratory Study of Adolescents in Turkey

Abstract: Adolescence is a time of rapid development and change. In this developmental period, adolescents have to struggle with a large number of stress factors. In this process resilience is important to have as an adaptive, stress-resistant personal quality. The recent research considers that numerous factors contribute to resilience in adolescents; the internal characteristics associated with resilience include such as self-esteem, self-efficacy, perseverance, internal locus of control, coping and adaptation skills.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 42 publications
1
29
0
7
Order By: Relevance
“…We also found that self-esteem was positively associated with resilience and negatively associated with stress. These study findings are consistent with prior research on the relationship of self-esteem with resilience (Arslan, 2015;Karatas & Cakar, 2011), and self-esteem with stress (Bi et al, 2016;Mann et al, 2004).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We also found that self-esteem was positively associated with resilience and negatively associated with stress. These study findings are consistent with prior research on the relationship of self-esteem with resilience (Arslan, 2015;Karatas & Cakar, 2011), and self-esteem with stress (Bi et al, 2016;Mann et al, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…Thus enhanced self-esteem increases levels of resilience (Karatas & Cakar, 2011). Also, Self-esteem has a close relationship with stress, and self-esteem is more likely to reduce stress levels (Bi et al, 2016).…”
Section: Self-esteem As Mediatormentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, students' levels of resilience were found to differ significantly based on the school that the child currently attends, the child's age, number of siblings, family's monthly income, mother's level of education, parents' professions, where the child's father grew up, level of protective attitude adopted by the parents, and the attitude adopted by the parents while bringing up the child. Karatas and Savi-Cakar (2011) found that self-esteem and hopelessness are significant predictors of resilience in adolescents. Savi-Cakar and found that the social support perceived by adolescents predicts their level of resilience significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Existen igualmente trabajos realizados con muestras de adolescentes y jóvenes (Benetti y Kambouropoulos, 2006;Cardozo y Alderete, 2009;Dumont y Provost, 1999;Karatas y Savi Cakar, 2011) o con menores infractores (Kidd y Shahar, 2008), que sugieren la existencia de conexión directa entre ambas variables. Puede presuponerse, por tanto, que entre los aspectos individuales que distinguen a la persona que afronta eficazmente la adversidad, la autopercepción positiva ocupa un lugar preferente.…”
Section: Introductionunclassified